1978
DOI: 10.1037/h0081669
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of pattern-analyzing skills in reading.

Abstract: Two groups of college students named letters or read text as training for subsequent naming letters or reading text. The main findings were that naming letters was good practice for further letter-naming and also quickened speed of reading text, but not as much as reading itself did. Reading text was good practice for further reading, did not quicken naming letters, but did increase accuracy. The results show why neither the analytical nor the whole word approach to visual pattern training in literacy is domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

1980
1980
1989
1989

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 7 publications
2
23
1
Order By: Relevance
“…The two training tasks had about the same influence on subsequent ability to name isolated scrambled letters, moreover. The contrast with the results found by Kolers and Magee (1978) is marked. Their subjects either named letters or read text as practice for later reading or letter naming.…”
Section: Methodscontrasting
confidence: 55%
See 1 more Smart Citation
“…The two training tasks had about the same influence on subsequent ability to name isolated scrambled letters, moreover. The contrast with the results found by Kolers and Magee (1978) is marked. Their subjects either named letters or read text as practice for later reading or letter naming.…”
Section: Methodscontrasting
confidence: 55%
“…That is, it argues for recognition of letters, not their order letters separated by spaces. A very important difference between the two studies is that the Kolers and Magee (1978) study trained subjects on passages of letters that were separated, each letter followed by a blank space; in the present study the training letters were aggregated into pseudowords. So we found that practice at naming letters that are assembled into sequences transfers only moderately to naming individualized letters.…”
Section: Discussionmentioning
confidence: 99%
“…(This is illustrated by the plus sign in Figure 11.) Thus, when context cues are unavailable-for tests across sessions or over the course of a year in our studies-then facilitation will decrease or even disappear (e.g., Jacoby, 1983a, Experiments 2 and 4; Jacoby, 1983b;Jacoby & Brooks, 1984;Kolers, 1976;Kolers & Magee, 1978; but see also Jacoby, 1983a, Experiment 3).…”
Section: A Proposed Model Of Identificationmentioning
confidence: 99%
“…Or, could the transfer between tasks be at some lower level of analysis, such as the transfer of visually specific processing skills? Kolers and his colleagues (Kolers & Magee, 1978;Kolers, Palef, & Stelmach, 1980) have studied the general transfer from different types of practice to subsequent reading tasks. They have reported maximal transfer to text reading when practice was given on reading orthographically regular letter sequences or words, rather than single letters.…”
Section: Experiments 2amentioning
confidence: 99%